Effects of Exogenous Application of Osmotic Adjustment Substances on Growth, Pigment Concentration, and Physiological Parameters of Dracaena sanderiana Sander under Different Levels of Salinity - Pedro García-Caparrós (Agronomy, 2020)
We evaluated two osmotic adjustment substances (glycine betaine (GB) and glycine (G) and a combination of both glycine + glycine betaine (G + GB) using two modes of application; irrigation and foliar sprays with Dracaena sanderiana plants. The plants were grown in containers and subjected to two levels of NaCl concentrations (2.0 and 7.5 dS m−1) over 8 weeks. Growth, pigment concentrations, and physiological parameters were assessed at the end of the trial. The foliar application of GB resulted in most optimal plant growth and biomass production in the presence of NaCl. The chlorophyll and carotenoid concentrations showed different trends depending on the osmotic adjustment substance applied and the mode of application. Stomatal density and dimensions varied considerably with respect to the osmotic adjustment substance supplied. The concentration of soluble sugars in leaves did not show a clear trend under the different treatments assessed. The exogenous application of G resulted in the highest concentration of free proline and proteins in leaves. The antioxidant capacity in leaves increased with both osmotic adjustment substances, and both means of application, under low and high saline conditions. We concluded that the foliar application of GB can be recommended in order to achieve cost-effective growth of D. sanderiana under saline conditions.